Law and Professional Issues in Nursing - Griffith, Richard (Richard A.); Tengnah, Cassam (2023)
This is an essential resource for student nurses as they begin to develop their knowledge and understanding of the requirements for safe practice in healthcare.
"Mapped to the 2018 NMC standards"--Front cover.
Previous edition: 2020.
Includes bibliographical references and index.
Keywords: Nursing ethics -- Great Britain; Nursing -- Law and legislation -- Great Britain; Law